Internet Addiction and Acculturative Stress Among International College Students in the United States - Li, Jason; Liu, Xun (Journal of International Students, 2021)
While Internet use plays an increasingly important role in individuals’ lives, many college students have found themselves totally unconsciously plunged into Internet addiction (IA). Guided by the acculturative stress theory, we examined the relationships between acculturative stress, gender, age, length of stay, and IA among international college students. Data were collected from 111 international undergraduate and graduate students studying in the United States. Hierarchical multiple regression analyses reported that acculturative stress and gender significantly predict IA among international college students. In this sample, neither age nor length of stay predicted IA. Our findings paint a picture of the potential influence of acculturative stress on IA. We offer suggestions for future research on Internet addiction and acculturative stress, particularly for international college students.